(untitled) (Journal of the Spanish Institute for Strategic Studies, 2021)
The alliance between the United States and Saudi Arabia has been in force for over seventy years, but the paradigms on which it based on having suffered numerous tensions in recent decades. The Saudi State and House of Saud carry on being important political and economic partners of the US Administration in the Middle East and the Muslim world, although the differences between the two countries looks like more evident nowadays. In the course of the presidencies of George W. Bush and Barack Obama, there was a clear distancing from their Arab ally, due to the deep division of interests on issues as sensitive as security and defense. In the first years of Donald Trump’s term, relations with the Saud crown seem to be better, blending efforts to counteract possible threats in the local scenary. This article analyzes the changes in the relationship between the two allies and the points of interest in the regional agenda of both.